PENGEMBANGAN E-MODUL FLIPBOOK MATERI HIDANGAN BUAH LOKAL MODEL PROJECT BASED LEARNING MATA PELAJARAN MUATAN LOKAL TATA BOGA - Maharani, Rachel Tania; Nur Qudus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to analyze the development process, feasibility, practicality, and effectiveness of a flipbook e-module based on the Project Based Learning (PjBL) model on the topic of Local Fruit Dishes for eleventh-grade students at SMK Tarunatama Getasan. The study was motivated by students' low learning enthusiasm, the lack of attractive instructional media, and the limited availability of systematic and contextual teaching materials. This research employed the Research and Development (R&D) method using the 4D model, consisting of Define, Design, Develop, and Disseminate stages. Data were collected through observations, interviews, expert validation sheets, student response questionnaires, and learning achievement tests in the form of pretests and posttests. The research subjects consisted of material experts, media experts, subject teachers, and eleventh-grade students of SMK Tarunatama Getasan. The findings revealed that the developed flipbook e-module was considered highly feasible based on the material expert validation results, obtaining an Aiken's V value of 0,829 and a feasibility percentage of 84,67%. Meanwhile, media expert validation resulted in an Aiken's V value of 0,875 with a feasibility percentage of 90%. The practicality assessment based on students' responses showed an average percentage score of 78,38%, which was categorized as good and feasible. The effectiveness test indicated that the average N-Gain Score of the experimental class was 61,78%, categorized as moderately effective, whereas the control class obtained an average score of 32,65%, categorized as ineffective. Furthermore, the Independent Samples T-Test yielded a significance value of 0,528 (> 0.05), indicating that both classes had equivalent initial abilities before the treatment was implemented. Based on these findings, it can be concluded that the PjBL-based flipbook e-module on Local Fruit Dishes is feasible, practical, and effective for use in the Local Content Culinary Arts learning process at SMK Tarunatama Getasan.